Structured porous blunt trailing edge with uniform and non-uniform parameters for vortex shedding noise reduction. (April 2023) - Liu, Hanru; Hu, Zhijie; Chen, Nanshu; Liu, Yu; Fan, Hengwei
Highlights: The structured porous media provide significant reduction of vortex shedding noise. Unexpected mid-high frequency noise is caused by cavity resonance of porous scale. Larger volume-averaged porosity is responsible for better shedding tone suppression. Proper porosity distribution simultaneously attenuates the mid-high frequency noise. Weakened vortex intensity of shear layer and delayed shedding are crucial mechanisms. Abstract: Aiming at reducing the blunt trailing edge noise of flat plate, three-dimensional structured porous media with uniform and non-uniform porosities are designed. Acoustics and flow measurement using far-field microphone and particle image velocimetry (PIV) respectively have been implemented in the anechoic wind tunnel to investigate the mechanisms of noise reduction and flow manipulation. The chord-based inflow Reynolds numbers range from 4.8 × 10 5 to 1.5 × 10 6 . The present work reveals that the regularized structured porous media could provide an effective noise reduction for the blunt trailing edge of flat plate similar to conventional randomized porous media ( e.g . metal foam). When the uniform porosity is larger than 0.73, the tonal noise is suppressed significantly and the overall sound pressure level is decreased by 10 dB at least. However, some unexpected additional noise in the mid-to-high frequencies (1500–9000 Hz) occurs, which is associated with primary flow interactions inside the pore structures (cavity resonance). Further, four non-uniform porosity cases are studied to explore the optimization of porosity distribution. Not only is the tonal noise significantly reduced but also the additional noise is lower than that of uniform cases, which indicates that non-uniform porosity has more potential advantages for noise reduction. It is interestingly discovered that for the non-uniform porous trailing edge, the volume-average porosity and distribution trend play important roles respectively in suppressing the tonal noise and the additional mid-to-high-frequency noise. The PIV results demonstrate that 3D printed structured porous media can significantly weaken the vortex intensity of the shear layer and delay the generation of vortex shedding downstream, which are the critical underlying mechanisms for noise reduction. The porosity of uniform cases and the volume-average porosity of non-uniform cases are closely associated with the vortex shedding and the high-values benefit of suppression. And the analysis of wake velocity spectrum indicates that the additional noise is not correlated to the wake flow, but the cavity resonance might be the main reason.